CVP Analysis and Break-even Assessment of the Enterprise ("Journal "U". Economy. Management. Finance.", 2021)
The article is devoted to the assessment of production break-even by the CVP-analysis method, which helps to understand the relationship "cost-volume-profit". The methodology for calculating the break-even point is investigated, which is based on the marginal approach to consider the costs of the enterprise.
Keywords: CVP - analysis (costs-volume-profit); schedule and break-even point; variable costs; fixed costs; revenue; price; production volume; cost price; profit margin